Cohort study from 11 European countries highlighted differences in the use and efficacy of hypothermia prevention strategies after very preterm birth - Wilson, E (2018)
AIM: This study investigated the different strategies used in 11 European countries to prevent hypothermia, which continues to affect a large proportion of preterm births in the region. METHODS: We examined the association between the reported use of hypothermia prevention strategies in delivery rooms and body temperatures on admission to neonatal intensive care units (NICUs) in 5861 infants born at 22 + 0 to 31 +6 weeks of gestation. The use of plastic bags, wraps, caps, exothermic heat and mattresses was investigated. RESULTS: The proportion of infants born in units that systematically used one or more hypothermia prevention strategies was 88.2% and 50.9% of those infants were hypothermic on admission to NICUs. Of the 9.6% born in units without systematic hypothermia prevention, 73.2% were hypothermic. Only 2.2% of infants were born in units with no reported prevention strategies. Lower gestational age increased the probability of hypothermia. No significant differences were found between the various hypothermia prevention strategies. Hyperthermia was seen in 4.8% of all admitted infants. CONCLUSION: Very preterm infants had lower risks of hypothermia on NICU admission if the unit used systematic prevention strategies. All the strategies had similar effects, possibly due to implementation rather than a strategy's specific efficacy.